2020
DOI: 10.1155/2020/3897168
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress of the Application of Hypothermia in the Eye

Abstract: Hypothermia is widely used in the medical field to protect organs or tissues from damage. Different research fields have different explanations of the protection mechanism of hypothermia. Hypothermia is also widely used in the field of ophthalmology, for example, in the eye bank, the preservation of corneal tissue and the preservation of the eyeball. Low temperature can also be applied to some ophthalmic diseases, such as allergic conjunctivitis, retinal ischemia, and retinal hypoxia. It is used to relieve eye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 97 publications
0
7
0
Order By: Relevance
“…Recent reviews have linked the experimental data obtained in animals and the potential applications of hypothermia for preventing neural damage, including retinal injury, in human newborns (Albrecht et al, 2019;Xi 2020). Interestingly, many native cultures around the world practice dipping newborns in cold water soon after birth (Connell-Szasz 1988;Degefie et al, 2014;Sacks et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Recent reviews have linked the experimental data obtained in animals and the potential applications of hypothermia for preventing neural damage, including retinal injury, in human newborns (Albrecht et al, 2019;Xi 2020). Interestingly, many native cultures around the world practice dipping newborns in cold water soon after birth (Connell-Szasz 1988;Degefie et al, 2014;Sacks et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…While induction of systemic hypothermia can be associated with significant adverse effects such as shivering, hypotension, cardiac arrhythmias, pneumonia, and thrombocytopenia, locally induced ocular hypothermia could prevent these. 88 In the eye and retina, localized hypothermia can be achieved during vitrectomy using hypothermic saline at the desired temperature; one can use the infusion fluid during vitrectomy to achieve this hypothermia if a known pre-operative temperature target is determined. We have called this “Hypothermic Vitrectomy”.…”
Section: Non-pharmacologic Neuroprotective Strategies For Craomentioning
confidence: 99%
“…While induction of systemic hypothermia can be associated with significant adverse effects such as shivering, hypotension, cardiac arrhythmias, pneumonia, and thrombocytopenia, locally induced ocular hypothermia could prevent these. 88 In the eye and retina, localized hypothermia can be achieved during vitrectomy using hypothermic saline at the https://doi.org/10.2147/OPTH.S403433…”
Section: Non-pharmacologic Neuroprotective Strategies For Craomentioning
confidence: 99%
“…Currently, three forms of preservation of corneal grafts are used – organ culture solution (28–37°C), hypothermia (2–8°C), and cryopreservation (4°C). 1 Of these, hypothermia is most frequently used in the United States, while European eye banks more frequently use organ culture. Organ culture, in which tissue is incubated in a medium supplemented with fetal calf serum, antibiotics, and antimycotics, has been associated with longer viable storage times than hypothermia.…”
Section: Introductionmentioning
confidence: 99%
“…Organ culture, in which tissue is incubated in a medium supplemented with fetal calf serum, antibiotics, and antimycotics, has been associated with longer viable storage times than hypothermia. 1 However, surgeons and eye banks have become judicious with the number of days a corneal graft can be used after preservation, with many preferring not to exceed seven days when stored via hypothermia. 2 Despite this, many recent studies have found few significant associations between the preservation characteristics of the graft and corneal transplantation outcomes.…”
Section: Introductionmentioning
confidence: 99%